Tensiomyography of selected lower-limb muscles in professional soccer players - Rey, E.; Lago-Penas, C.; Lago-Ballesteros, J. (Journal of Electromyography and Kinesiology, 2012)
Tensiomyography is a non-invasive method of neuromuscular assessment used to measure muscle action characteristics, muscle tone, and muscle fiber type, and provides information on acute and chronic responses of muscle to different training loads. The aims of the present study were: to analyse differences in muscle response and mechanical characteristics of two major muscles of the lower extremity in a large group of Spanish soccer players according to playing position, and to provide group norms against which clinical findings may be compared. Data were collected from 78 professional soccer players (age 26.6 ± 4.4 years; height: 179.2 ± 5.3 cm; body mass: 75.8 ± 5.3 kg). Tensiomyography was recorded from the rectus femoris (RF) and biceps femoris (BF) muscles after 2 days without take part in any strenuous exercise or training. Five tensiomyographic parameters were analyzed: maximal displacement (Dm), contraction time (Tc), sustain time (Ts), delay time (Td), and half-relaxation time (Tr). A good to excellent intra-session reliability was found for all contractile parameters (ICC ranged from 0.78 to 0.95). No significant differences between players of any position were observed in absolute values of BF. However, significant differences were observed for Tc, Tr and Ts between the different playing positions on RF (P < 0.05, effect size ranged from 1.3 to 1.6). Professional soccer players showed muscles with ability to rapidly generate force during contractions. The neuromuscular profile provided could help in identifying the normative data that are important for the different positions in order to optimize the training and recovery process of each individual player.